(Photo)Thermal Stimulation of Functional Dithiolene Complexes in Soft Matter. Issue 6 (30th January 2020) - Camerel, Franck; Fourmigué, Marc
Abstract : Square‐planar bis(dithiolene) complexes are characterized with a planar delocalized structure and a strong and tunable near infrared (NIR) absorption; they are highly stable under laser irradiation, and their conversion efficiency (light to heat) reaches up to 40–50 %. Their involvement in soft matter, namely liquid crystals, gels, and nanoparticles, opens many possibilities to control the actual state of a material, particularly under light irradiation. Thus, liquid crystalline phases can easily be modified, (i) with temperature to modulate the extended magnetic interactions of paramagnetic complexes, or (ii) under laser irradiation to unravel these remarkable photothermal properties, toward the development of light‐responsive materials. Dithiolene complexes can be also functionalized to produce very effective gelation agents, while the photothermal effect can be used to destabilize at will their supramolecular organization. Besides photothermal therapy, new therapeutic agents were also developed for photo‐controlled drug delivery and bioimaging, combining chemotherapy and phototherapy. Hydrophobic complexes were accordingly designed for their encapsulation in block copolymer nanoparticles for photothermal therapy and photo‐controlled drug delivery under laser irradiation. This class of complexes can be also used as exogenous contrast agents for photoacoustic bioimaging. Abstract : Proper functionalization of metal‐bis(dithiolene) complexes enables the development of stimuli‐responsive soft materials for applications in biotechnology and materials science.